Cognitive Skills, Gender and Risk Preferences1. Issue 284 (17th January 2013) - Booth, Alison L.; Katic, Pamela
<x xml:space="preserve">Abstract</x> In this study, we utilise data from a unique new birth‐cohort study to see how the risk preferences of young people are affected by cognitive skills and gender. We find that cognitive ability (measured by the percentile ranking for university entrance at age 18) has no effect on risk preferences measured at age 20. This is in contrast to experimental studies that use IQ measures to proxy cognitive skills. However, we do find that gender matters. While young women are significantly more likely than young men to assess themselves as being prepared to take risks, women choose to invest significantly less when they are confronted with a clearly specified investment decision based on hypothetical lottery winnings. This difference between the impact of gender on risk attitudes and the hypothetical lottery investment suggests that impatience and framing affect young women and men differently.